2021
DOI: 10.1007/s11356-021-13214-z
|View full text |Cite
|
Sign up to set email alerts
|

Vermicomposting of harvested waste biomass of potato crop employing Eisenia fetida: changes in nutrient profile and assessment of the maturity of the end products

Abstract: Vermicomposting potential of waste biomass of potato crop that are generated at the time of harvesting was studied employing Eisenia fetida. The experiment was carried out in pots taking two treatments; in one only potato plant biomass (PPB) was taken as raw materials whereas in the other a mixture of PPB with cow dung was engaged in the proportion of 5:1. The vermicomposted materials showed a reduction in C/N ratio, humi cation index, enhancement in nutrients pro les, ash contents, nitrogen-xing, phosphate an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Humi cation index is an indicative parameter for compost/vermicompost stabilization (Das and Deka 2021). The decreasing trend in HI level after vermicomposting process has already been reported by earlier workers (Negi and Suthar 2018;Boruah et al 2019).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Humi cation index is an indicative parameter for compost/vermicompost stabilization (Das and Deka 2021). The decreasing trend in HI level after vermicomposting process has already been reported by earlier workers (Negi and Suthar 2018;Boruah et al 2019).…”
Section: Discussionmentioning
confidence: 57%
“…For example, urease and dehydrogenase activities are measured to assess the impact of microbial community and role of urea during the vermicomposting process (Yadav et al 2015;Pellejero et al 2020;Srivastava et al 2020). Similarly, the humi cation index is found to be reliable and well used parameters to study the vermicompost stability (Das and Deka 2021). Upon the decomposition of substrate the humi cation index gets reduced and gives the idea regarding degree of degradation, oxidation and decomposition (Lim et al 2015b;Ganguly and Chakraborty 2019) of the vermicomposting substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The final pH values of both the coprolites from GS and GM were slightly acidic to alkaline attributed to gut microbial activity, indicating that these coprolites could be useful to remediate soil reaction. Vermicomposting of fruit and vegetable wastes 81 , 82 ; seaweeds, sugarcane trash, coir pith amended with cow dung 83 ; and flowering plants ( Lantana camara ) 84 was also reported to produce vermicompost with a pH close to neutral. Analyses of variance for total organic carbon indicated significant ( p < 0.05) differences between the coprolites from GS (18.24%) and GM (27.18%) with their controls GS (control) (29.42%) and GM (control) (32.02%) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The micro-organisms require N for their growth, so they break down the organic materials and release nutrients. This process involves immobilization of N from the soil by the micro-organisms (Das and Deka, 2021). However, Geng et al (2019) found that application of different composted organic residues significantly increased the N, P and K uptake by corn plants over control and the increase was proportional to the increase in the composted organic residues rates.…”
Section: Discussionmentioning
confidence: 99%